2016
DOI: 10.1177/0267659115616179
|View full text |Cite
|
Sign up to set email alerts
|

The scientific evidence of arterial line filtration in cardiopulmonary bypass

Abstract: ALF is a standard implemented in a majority of cardiopulmonary bypass procedures in Europe. The level of scientific evidence available in support of current arterial line filtration methods in cardiopulmonary bypass is, however, poor. Large, well-designed, randomised trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In Europe, Johagen and Svenmarker's survey revealed a widespread adoption of ALFs, primarily to thwart arterial embolization, indicating a global consensus on their utility as a preventative tool against GME. 13 The introduction of integrated arterial filters with oxygenators has spurred a new wave of research, examining their impact on CPB outcomes. Sathianathan et al's in-vitro evaluation of neonatal CPB circuits highlighted the benefits of circuit miniaturization in reducing hemodilution and inflammatory responses, despite the potential for GME to cause undetected long-term neurological damage during complex cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, Johagen and Svenmarker's survey revealed a widespread adoption of ALFs, primarily to thwart arterial embolization, indicating a global consensus on their utility as a preventative tool against GME. 13 The introduction of integrated arterial filters with oxygenators has spurred a new wave of research, examining their impact on CPB outcomes. Sathianathan et al's in-vitro evaluation of neonatal CPB circuits highlighted the benefits of circuit miniaturization in reducing hemodilution and inflammatory responses, despite the potential for GME to cause undetected long-term neurological damage during complex cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably the first study to characterise the filterability of a single filter screen. Previous investigations have mainly addressed efficacy measures of conventional ALF components (3, 10). Our main objective was to broaden our understanding of GME filtration by introducing a new research strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree to which ALF protects the patient against arterial embolisation remains debatable. The scientific evidence in support for its use is surprisingly weak (3). ALF had a major protective function in combination with the use of bubble oxygenators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 5 12 The addition of arterial line filters in cardiopulmonary bypass circuits reduced gaseous microemboli and neuropsychologic impairment and has since become a standard in cardiac bypass surgery worldwide. [12][13][14][15] Perthel et al found that insertion of an inline arterial dynamic bubble trap in cardiac bypass circuit tubing reduced microbubbles by 65% and TCD microembolic signals in the middle cerebral artery by 86%. 14 A prospective study compared post-procedural DWI lesions in patients undergoing cerebral angiography with and without the addition of air microemboli filters placed between the catheter and flush line and the catheter and contrast injection port.…”
Section: Catching Bubblesmentioning
confidence: 99%